Território e mídia: cannabis na imprensa digital - (:unkn) unknown (Universidade Federal de Goiás, 2019)
This research seeks to theorize about the relationship cannabis x man, deepening in this world of divergence of opinions and foundations presented in scientific works and especially in the news published in digital media G1 Notícias and Carta Capital. The methodological theoretical effort undertaken here concerns the application of discourse analysis described by Foucault, along with the development of the discussion about territory, by authors such as Raffestin and Haesbaert. The proposal is to reflect on the formation of public opinion in relation to Cannabis from the news conveyed in the aforementioned digital media and also to understand the territorial arrangements created according to the needs of each historical moment. Therefore, we enter the social trajectory of cannabis, taking a historical perspective of the use, interest and its prohibition in the world, we go through the concepts of territory, media and discourse and start to analyze the recurrent medicinal and criminal statements in the media. G1 Notícias e Carta Capital. Understanding “media” for all media of information diffusion that constitutes an intermediate means of expression capable of transmitting messages and as a set of mass media, such as cinema, the press, communication satellites, electronic media and other media. / the telematics and recalling some periods of history, such as the Military Dictatorship, it became evident the role played by the media with regard to social control, which was / is more than a disseminator of information, being considered an opinion maker, Since newspapers and magazines are responsible for the production and circulation of informative content and their function is not only the social communication, but also to disseminate positions of subjects and influence the construction of the senses, acting as a private apparatus influenced and controlled by institutions and institutions. ruling classes. In view of the study, it became possible to infer the importance of studying the media with regard to social control to understand the environment internally and externally as competences of the geographer, as this is a dialectical movement that includes production, circulation and consumption. / decoding of news and facts. Finally, it can be concluded that Brazil is not prepared for the ban, since the number of people (young) incarcerated and killed in this process is alarming, and it can be seen that the war on drugs has failed worldwide, already that illegality allows the emergence of a trafficker's monopoly and this results in territorial conflicts in which organized crime articulates the control of the territory, the flow of drugs and, consequently, of consumers.
Territory and media: cannabis in the digital press
Keywords: Território; Poder; Mídia; Enunciado; Cannabis; Territory; Power; Media; Statement; Cannabis; CIENCIAS HUMANAS::GEOGRAFIA